2009
DOI: 10.1152/jn.91207.2008
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Spontaneous and Evoked Spike-Time Correlations in Primate Visual Cortex

Abstract: Coincident spikes have been implicated in vision-related processes such as feature binding, gain modulation, and long-distance communication. The source of these spike-time correlations is unknown. Although several studies have proposed that cortical spikes are correlated based on stimulus structure, others have suggested that spike-time correlations reflect ongoing cortical activity present even in the absence of a coherent visual stimulus. To examine this issue, we collected single-unit recordings from prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
28
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 71 publications
13
28
2
Order By: Relevance
“…Several reports describe significant relationships between correlation magnitudes and average firing rates such that higher correlation magnitudes tend to occur when the two neurons in the pair have higher average firing rates (e.g., de la Rocha et al 2007;Greenberg et al 2008;Jermakowicz et al 2009), although others report very weak relationships (Samonds and Bonds 2005). Our data showed weak, positive relationships overall; however, this trend occurred primarily when nonadjacent digit locations were stimulated (Fig.…”
Section: Relationship Of Correlation Magnitude and Average Firing Ratesupporting
confidence: 42%
See 2 more Smart Citations
“…Several reports describe significant relationships between correlation magnitudes and average firing rates such that higher correlation magnitudes tend to occur when the two neurons in the pair have higher average firing rates (e.g., de la Rocha et al 2007;Greenberg et al 2008;Jermakowicz et al 2009), although others report very weak relationships (Samonds and Bonds 2005). Our data showed weak, positive relationships overall; however, this trend occurred primarily when nonadjacent digit locations were stimulated (Fig.…”
Section: Relationship Of Correlation Magnitude and Average Firing Ratesupporting
confidence: 42%
“…Geometric mean spike rate is commonly used to average firing rates of the two neurons in a correlated pair (e.g., Bair et al 2001;de la Rocha et al 2007;Greenberg et al 2008;Jermakowicz et al 2009). We took the average firing rate of each neuron during the epoch when the correlation was measured (0 to 700 ms).…”
Section: Relationship Of Correlation Magnitude and Average Firing Ratementioning
confidence: 99%
See 1 more Smart Citation
“…We found that population responses to different stimuli are subject to conserved spatiotemporal constraints, consistent with results in other modalities indicating conserved timing patterns in pairwise cross-correlograms [ 25 ]. One can imagine a number of ways in which the physical properties of a neural circuit could impose consistent constraints on the spike patterns it can generate.…”
Section: Possible Mechanisms Of Packet Formationsupporting
confidence: 83%
“…8.2h ; R unanesth: spont-ton = 0.53 ± 0.17; p < 0.001). Similar consistent temporal patterns were also observed in the somatosensory cortex [ 9 ] and in the visual cortex [ 25 ] indicating that the sequential structure of spontaneous and evoked packets is a general feature of cortical processing.…”
Section: Similarity Of Sequential Spiking Activity Of Stimulus-evokedsupporting
confidence: 75%